Wykorzystanie metod porządkowania obiektów przy podejmowaniu decyzji dotyczących termomodernizacji budynków mieszkalnych - Foryś, Iwona (The Using Ordering of Objects Methods at the Starting House Buildings Termomodernization Decisions, 2007)
In this article author used the ordering of objects methods in the process of decisions connected with the choosing a house buildings to termomodernization. The author divided 37 objects on four groups, using the synthetic measure of the energy-effectivity in three heating seasons in years 2003-2006. In the group IV were found objects which had worst energy- parameters, instead in the group I - the best. In following heating seasons the arrangement gave nearing effects, and dislocatings in groups got out of executed on given objects in this time of termomodernization works. Dislocatings to higher groups, followed as result of of making worse of diagnostic quality, accepted in the analysis. The using synthetic measure of the development to the classification of objects according to the constant pattern gives property managers the simple tool of the type inference of following objects to termomodernization.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 385-392